Wpływ właściwości osadów ściekowych na możliwość ich termicznego unieszkodliwiania = Influence of sewage sludge properties on the thermal management processes - Werle, Sebastian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The analysis of various biomass materials indented to be used as fuel thermal processes has shown that there is always a range of the results sometimes with a big gap between minimum and maximum. Most noticeable for the sewage sludge was the highest share of ash, nearly 50% of the dry substance, compared to all the other fuels.
Keywords: osady ściekowe; spalanie; zgazowanie; piroliza; sewage sludge; combustion; gasification; pyrolysis